Cadmium sulfide thin films growth by chemical bath deposition. (March 2018) - Hariech, S.; Aida, M. S.; Bougdira, J.; Belmahi, M.; Medjahdi, G.; Genève, D.; Attaf, N.; Rinnert, H.
Abstract: Cadmium sulfide (CdS) thin films have been prepared by a simple technique such as chemical bath deposition (CBD). A set of samples CdS were deposited on glass substrates by varying the bath temperature from 55 to 75 °C at fixed deposition time (25 min) in order to investigate the effect of deposition temperature on CdS films physical properties. The determination of growth activation energy suggests that at low temperature CdS film growth is governed by the release of Cd 2+ ions in the solution. The structural characterization indicated that the CdS films structure is cubic or hexagonal with preferential orientation along the direction (111) or (002), respectively. The optical characterization indicated that the films have a fairly high transparency, which varies between 55% and 80% in the visible range of the optical spectrum, the refractive index varies from 1.85 to 2.5 and the optical gap value of which can reach 2.2 eV. It can be suggested that these properties make these films perfectly suitable for their use as window film in thin films based solar cells.